Early Miocene detrital zircon age from fluvial deposits of La Marcelina Formation in the Deseado Massif, Southern Patagonia, Argentina - Aramendía, Inés (2024)
The La Marcelina Formation (LMF) in the southern Deseado Massif area (c. 47° 55' S) represents a 23 m thick sedimentary succession deposited within a low-energy fluvial paleoenvironment. The age of this unit, formerly considered as Eocene due to its palynological assemblage, is adjusted by zircon U-Pb Laser Ablation-Inductively Coupled Plasma-Mass Spectrometry (LA-ICP-MS) from a sandstone bed at the middle part of the unit. The results reveal a maximum depositional age of ~20 Ma (Early Miocene, Burdigalian). The detrital zircon provenance analysis indicates zircon grains originated mostly in the Jurassic, with limited contributions from the Cretaceous, Permian, and Paleocene. The new age for LMF allows correlating these beds to the upper section of the continental Río Leona Formation in the southern Austral-Magallanes Basin.